Rover Science Autonomy in Planetary Exploration: Field Analog Tests - Eldar Z. Noe Dobrea; Maria E. Banks; Roger N. Clark; David Wettergreen; Alberto Candela; Amanda Hendrix; Caitlin Ahrens; Ernie Bell; Abigail Breitfeld; Thomas F. Bristow; Sanlyn Buxner; Margaret Hansen; et al. (The Planetary Science Journal)
A strategy for planetary exploration using a rover capable of science autonomy is presented. We encoded into a rover a set of driving hypotheses pertaining to the geologic origin of a field site and equipped the rover with the instrumentation needed to measure the observables related to the hypotheses, as well as the software tools to analyze them to a relatively high level of confidence. We investigated the effects of different exploration strategies that make use of rover science autonomy and compared the operational efficiency and science yield of three geological exploration scenarios: (1) standard human-directed exploration, (2) rover-directed exploration, and (3) astronaut/rover collaborative exploration. We show that exploration with a rover capable of science autonomy is operationally more efficient than the human-directed strategy, resulting in higher rates of data collection and hence a greater science yield per command cycle. Additionally, we explored and developed astronaut/rover collaborative exploration strategies and present a basic framework for effective planetary exploration that leverages the expertise of a science team, the efficiency of a science-autonomous rover, and the contextual abilities of astronauts.